Pemujaan Lingga Dalam Kontek Simbolisasi Ida Bhatara Lingsir Sanghyang Śiva Paśupati - I Nyoman Temon Astawa; I Wayan Suwadnyana (Jurnal Penelitian Agama Hindu, 2020)
Hinduism in worshiping God and all its manifestations, uses various media which are symbols of God's manifestation. These symbols include a stone or a pair of stones, a statue or pratima, a building or nature directly such as rivers, lakes, ponds, sea and mountains. Lingga is one form of worship facilities known by the Hindu community in Indonesia. The phallus worship is a form of worship of God Almighty in the form of the symbolization of Ida Bhatara Lingsir Sanghyang Śiva Paśupati.